ϒ suppression in PbPb collisions at √sNN=2.76 TeV - Nendzig, Felix; Wolschin, Georg (Nuclear physics. A, Nuclear and hadronic physics, 2013)
We suggest that the combined effect of screening, gluon-induced dissociation, collisional damping, and reduced feed-down explains most of the sequential suppression of ϒ(nS) states that has been observed in PbPb relative to pp collisions at sNN=2.76 TeV. The suppression is thus a clear, albeit indirect, indication for the presence of a qgp.
Im Titel ist "NN" nach "s" tiefgestellt, der ganze Ausdruck "sNN" steht unter dem Wurzelsymbol
Gesehen am 08.12.2021